Bariatric surgery outcomes in Medicare beneficiaries. (22nd December 2020) - Wirth, Keith; Kizy, Scott; Abdelwahab, Hisham; Zhang, Jianying; Agarwal, Santosh; Ikramuddin, Sayeed; Leslie, Daniel B.
Abstract: Background: The Medicare population is increasing while the prevalence of obesity remains high. Bariatric surgery is the most efficacious treatment of obesity and its comorbidities. The objective of this investigation was to assess trends in utilization, readmission, mortality, and cost of bariatric surgery in the Medicare population. Methods: Utilizing the Medicare Provider Analysis and Review database, patients with clinically severe obesity undergoing laparoscopic Roux‐en‐Y gastric bypass (RYGB), laparoscopic sleeve gastrectomy (SG), and laparoscopic adjustable gastric banding (LAGB) from 2011–2015 were identified. Trends in procedure selection, readmissions, mortality, and cost were examined. A multivariable logistic regression analysis to evaluate factors associated with readmission and mortality was performed. Results: Of the 73, 718 patients identified, 53, 949 (73%) of patients were enrolled in Medicare due to disability, 19, 191 (26%) due to age, and 578 (<1%) due to end stage renal disease (ESRD). Utilization of SG increased (1% in 2011 to 61% in 2015), while utilization of RYGB (68% to 32%) and LAGB (31% to 1%) decreased. Length of stay (LOS) was highest after RYGB (2.54 days), and lowest after LAGB (1.32 days). LOS decreased from 2.23 days in 2011 to 2.12 days in 2015. Thirty‐day readmissions were 8.24% for the disabled, 5.5% for the elderly, 12.8% with ESRD. Odds of readmission increased with black race, higher body mass index (BMI), and RYGB. Readmission decreased from 8% in 2011 to 7% in 2015. Thirty‐day mortality was 0.22% in the disabled, and 0.28% in the elderly. Odds of 30‐day mortality increased among men, those with higher BMI, some comorbidities, and those who underwent RYGB. Cost of SG decreased while cost of RYGB increased. Conclusions: Among the Medicare population, an increase in SG while a decrease in RYGB and LAGB utilization was noted from 2011–2015. Readmissions and cost have decreased, while mortality has remained low.